Cultural Relations in a New Century. Issue 2 (19th May 2022) - Rose, Martin
Abstract: This essay examines Ziauddin Sardar's ideas on Cultural Relations, and specifically his relationship with the British Council, primarily through two pieces of his writing, his 2004 British Council 70th Anniversary Lecture and an essay of the same year about being a British Muslim. It reflects on his concepts of "transmodernism" and "mutually assured dialogue" both as theoretical and as practical tools in Cultural Relations.